MANAGEMENT OF PHYSIOTHERAPY IN MITRAL VALVE REPLACEMENT E.C. MITRAL REGURGITATION RELATED TO AEROBIC CAPACITY: A CASE STUDY - Suwendra, Ria; Sari, Dwi Rosella Komala; Susilo, Ridwan Andi (Universitas Muhammadiyah Surakarta, 2021)
Introduction: A mitral regurgitation (MR) is the second most common single native valvular disease and accounts for 31.6% of valvular heart disease patients with degenerative etiology as much as 61.3%, rheumatism 14.2%, endocarditis 3.5%, inflammation 0.8%, congenital 4.8%, ischemic 7.3%, miscellaneous 8.1%.2 In patients who undergoing surgical intervention for severe MR, the most common etiologies being MVP (20%-70% of cases), ischemic MR (13%- 30% of cases), rheumatic disease (3%-40% of cases), and endocarditis (10%- 12% cases). Case presentation: A 44-year-old housewife patient complained of pain in the area around the operation of Dr. Moewardi’s hospital, Surakarta, especially when coughed and sneezed and body rotation involved movement in the chest area. Found muscle spasm in the area intercostals muscles, scaleni, levator scapula, and pectoralis major. On auscultation there was a clicking sound coming from a mechanical valve, no cardiac murmur was heard, percussion was resonant. laboratory test Fasting Blood Sugar 148 mg/dl, and other results look normal. Blood pressure was 108/46 mmHg, SPO2 was 98%, temperature was 36.8˚C, respiratory rate was 20 bpm, heart rate was 70 bpm. Vital examinations were performed before performing the strength test. Management and outcomes: Performed massage with efflurage technique to reduce spasm in the accessory muscles of respiration. The patient underwent a physiotherapy rehabilitation program using a 6 minutes walking test with telemetry. The exercise phase lasts about 20-60 minutes with the brisk walking exercise method. Borg Scale – RPE Category Scale was used to measure the perception of fatigue and dyspnea symptoms during exercise. Exercise is given 10 times in 2 weeks with one session of 60 minutes Disscussion: Physiotherapy technique as effleurage is an effective technique used to increase blood flow, reduce muscle tightness and relieve muscle tension. And walk brisk were able to reduce the fatique symptom of patient and increase the capability of tolerance activity. Although the aerobic capacity was not altering as well. Conclution: The regular exercises can significantly improve the quality of life in patient with post surgery mitral valve replacement.